How can we better serve adolescent key populations? Strategies to encourage and inform future data collection, analysis, and use†. Issue 8 (3rd August 2017) - Dayton, Robyn; Nary, Paul; Cunningham, Joy; Plourde, Kate F; Green, Kimberly; Wambugu, Samuel; Shrestha, Mahesh; Aiyenigba, Bolatito; Ngige, Evelyn
ABSTRACT: Young key populations (ages 10–24) (YKPs) are uniquely vulnerable to HIV infection. Yet they are often underserved, due in part to a limited understanding of their needs. Many successful approaches to understanding YKPs exist but are not widely used. To identify the most useful approaches and encourage their uptake, we reviewed strategic information on YKPs and experiences collecting, analysing, and utilising it from countries in Africa, Asia, and Central and Eastern Europe. As a result, we recommend one central guiding principle – any effort to understand and serve YKPs should include a specific focus on adolescent key populations (AKPs) (ages 10–19) – and three strategies to inform data collection, analysis, and use: tailor recruitment practices to ensure young people's representation, select indicators and research methods based on their ability to inform responsive programming for and give a voice to YKPs, and thoroughly disaggregate data. We demonstrate the utility of each strategy in YKP research and programmes, and in doing so note the particular importance for AKPs. We hope that this paper encourages additional research on YKPs and helps bridge the gap between research and effective programmes to serve the youngest and most vulnerable members of key populations.